2011
DOI: 10.1051/0004-6361/201014265
|View full text |Cite
|
Sign up to set email alerts
|

TRACE observations of driven loop oscillations

Abstract: Aims. On 13 June 1998, the TRACE satellite was fortuitously well placed to observe the effects of a flare-induced EIT wave in the corona, and its subsequent interaction with coronal magnetic loops. In this study, we use these TRACE observations to corroborate previous theoretical work, which determined the response of a coronal loop to a harmonic driver in the context of ideal magnetohydrodynamics, as well as estimate the magnetic field strength and the degree of longitudinal inhomogeneity. Methods. Loop edges… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Wills-Davey and have shown that the impact of a coronal EUV wave can excite these loop oscillations. Note that for a harmonic coronal wave, the dominant period of the resulting loop oscillation will belong to the driver, while a single-pulse disturbance will excite only natural periods of the loop (see Ballai et al, 2008Ballai et al, , 2011b.…”
Section: Excitation Of Oscillationsmentioning
confidence: 99%
“…Wills-Davey and have shown that the impact of a coronal EUV wave can excite these loop oscillations. Note that for a harmonic coronal wave, the dominant period of the resulting loop oscillation will belong to the driver, while a single-pulse disturbance will excite only natural periods of the loop (see Ballai et al, 2008Ballai et al, , 2011b.…”
Section: Excitation Of Oscillationsmentioning
confidence: 99%
“…These authors also showed that the deviation of P 1 /P 2 from 2 is proportional to the degree of stratification (see also, e.g. McEwan et al 2006;Van Doorsselaere et al 2007;Ballai et al 2011). Later, studies by, e.g.…”
Section: Introductionmentioning
confidence: 88%
“…Considerable advances have been achieved in diagnosing the state of the field and plasma (see, e.g. Roberts et al 1984;Nakariakov et al 1999;Nakariakov & Ofman 2001;Ofman & Thompson 2002;Ruderman & Roberts 2002;Andries et al 2005Andries et al , 2009Ballai et al 2005Ballai et al , 2011Gruszecki et al 2006Gruszecki et al , 2007Gruszecki et al , 2008Banerjee et al 2007;Ofman 2007Ofman , 2009McLaughlin & Ofman 2008;Verth et al 2007;Ballai 2007;Ruderman et al 2008;Van Doorsselaere et al 2008;Morton & Erdélyi 2009;Ruderman & Erdélyi 2009;Andries et al 2009;Selwa & Ofman 2009;. It is highly likely that higher resolution observations made possible recently by space A&A 537, A41 (2012) satellites such as STEREO, Hinode, SDO (and future missions) will further help understanding the complicated reality of the solar plasma environment.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of kink oscillations, they showed that the P 1 /P 2 period ratio can be different from the value of 2 that is obtained in the case of homogeneous loop, where P 1 represents the period of the fundamental transverse oscillation and P 2 is the period of the first harmonic of the same coronal loop. The degree of stratification is connected to this deviation of the P 1 /P 2 ratio from 2 (see, e.g., Andries, Arregui & Goossens 2005;McEwan et al 2006;Van Doorsselaere, Nakariakov & Verwichte 2007;Ballai, Jess & Douglas 2011). Period ratios other than 2 were already observed in coronal loops by, e.g.…”
Section: Introductionmentioning
confidence: 93%
“…One obvious use of these precise observation is the magneto-seismology of the solar atmosphere, were considerable progress has been achieved in coronal seismology (see, e.g. Roberts, Edwin, & Benz 1984;Nakariakov et al 1999;Nakariakov & Ofman 2001;Ofman & Aschwanden 2002;Ruderman & Roberts 2002;Andries, Arregui & Goossens 2005;Andries et al 2009;Ballai, Erdélyi & Pintér Corresponding author: b.orza@sheffield.ac.uk 2005; Ballai, Douglas & Marcu 2008;Ballai, Jess & Douglas 2011;Banerjee et al 2007;Verth et al 2007;Verth, Erdélyi & Jess, 2008;Ballai 2007;Ruderman, Verth & Erdélyi 2008;Ruderman & Erdélyi 2009;Selwa et al 2010;Orza et al 2012) but also in the diagnostics of the coupling of various solar atmospheric regions, e.g. the dynamical coupling of the photosphere, chromosphere and corona (e.g.…”
Section: Introductionmentioning
confidence: 99%